Promosi Olahraga Tinju Adat Etu Sebagai Pariwisata Tahunan di Kecamatan Boawae Kabupaten Nagekeo - Aschari Senjahari Rawe; Yohana Nono BS (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine how the implementation of Etu traditional boxing in Bhoawae sub-district and the promotion of this sport as a type of tourism in Nagekeo district, East Nusa Tenggara. This research is a qualitative descriptive study with 4 informants as the subject of the study. The data collection technique was carried out by in-depth interviews, documentation and observation. Data were analyzed using Miles Huberman's interactive analysis model. The results showed that the procedures for implementing the traditional Etu Boxing were carried out by traditional rituals and traditional dances. Boxers wear special equipment such as headbands, tai kolo, dhese and you gauze. Each round will end if one of the boxers has bleeding which symbolizes fertility. In conclusion, Etu is a boxing attraction that involves traditional rituals as an expression of gratitude for the people of the Bhoawae traditional village in welcoming the harvest, while the Etu promotion form currently being pursued by the government Nagekeo area is by making video story telling Keywords: Boxing, Adat Etu, Sports Promotion, Tourism